2003
DOI: 10.1128/jcm.41.12.5530-5536.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Outbreak of Infections by Proteus mirabilis That Produces Extended-Spectrum CTX-M-2 Type β-Lactamase

Abstract: Nineteen multidrug-resistant Proteus mirabilis strains were isolated from 19 patients suffering from infections probably caused by P. mirabilis. These strains were recovered from urine or other urogenital specimens of 16 inpatients and three outpatients with a hospitalization history in a urology ward of Funabashi Medical Center, from July 2001 to August 2002. These strains demonstrated resistance to cefotaxime, ceftriaxone, cefpodoxime, and aztreonam, while they were highly susceptible to ceftazidime (MIC, <0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…A diversity of ESBLs such as TEM-derived mutants was reported to be produced by P. mirabilis in Europe (Bonnet et al, 1999;Luzzaro et al, 2001;Biendo et al, 2005). CTX-M-2-, CTX-M-3-, CTX-M-13-and CTX-M-14-producing P. mirabilis has been reported in Hong Kong, Taiwan and Japan (Nagano et al, 2003;Ho et al, 2005;Wu et al, 2006). These data indicate a geographical feature of ESBL-producing P. mirabilis, with TEM types in Europe and CTX-M types in Eastern Asia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A diversity of ESBLs such as TEM-derived mutants was reported to be produced by P. mirabilis in Europe (Bonnet et al, 1999;Luzzaro et al, 2001;Biendo et al, 2005). CTX-M-2-, CTX-M-3-, CTX-M-13-and CTX-M-14-producing P. mirabilis has been reported in Hong Kong, Taiwan and Japan (Nagano et al, 2003;Ho et al, 2005;Wu et al, 2006). These data indicate a geographical feature of ESBL-producing P. mirabilis, with TEM types in Europe and CTX-M types in Eastern Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Uniquely, the species isolated in Japan possessed the CTX-M-2 enzyme frequently and predominantly in the Enterobacteriaceae. Previous studies have reported that ESBL-producing P. mirabilis in hospitals always encoded additional b-lactamase genes (Ho et al, 2005;Wu et al, 2006), with the exception of nosocomial outbreaks by ESBL-producing clonal strains (Nagano et al, 2003;Kim et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes were likely originally derived from beta-lactamases in Kluyvera ascorbata and are interesting in that they hydrolyze cefotaxime more rapidly than ceftazidime and are more readily inhibited by tazobactam than clavulanic acid or sulbactam (4). Strains expressing CTX-M enzymes have been responsible for outbreaks in Canada, South America, Asia and Europe (5)(6)(7)(8).…”
mentioning
confidence: 99%